THE APPLICATION OF ARTICLE 52 OF THE CRIMINAL CODE IN CORRUPTION DECISIONS (DECISION NUMBER 438K/PID. SUS/2021) - Grand Pilar Sinukaban, Chalxhes; Putra Frans, Mardian (JOURNAL EQUITABLE, 2026)
The one-third criminal penalty according to Article 52 of the Criminal Code against Civil Servants who abuse their positions is an essential but often neglected criminal law instrument in Indonesian corruption justice practice. This normative research analyzes the application of Article 52 of the Criminal Code in the imposition of corruption crimes through a study of Decision Number 438 K/Pid.Sus/2021. The results of the study show that although the defendant, a functional prosecutor, is proven to have committed corruption by abusing his position and authority, the provisions of Article 52 of the Criminal Code are not applied to all levels of justice—from district courts, appeals, to cassation. The absence of the application of this article weakens the deterrent effect and is contrary to the principle of accountability of public officials. The findings indicate systematic errors in the implementation of the law that have an impact on the legitimacy of the decision. The application of Article 52 of the Criminal Code must be an imperative juridical obligation, not a facultative option, to realize substantive justice and proportionality of criminal sanctions against state apparatus who abuse their positions.